Liquid electrolyte and lithium secondary battery

JP2025022740AActive Publication Date: 2025-02-14SAMSUNG SDI CO LTD +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024080892
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-01
Filing Date
2024-05-17
Publication Date
2025-02-14
Estimated Expiration
2044-05-17

AI Technical Summary

Benefits of technology

【0012】 問題発生時、電池のイオン伝導を遮断して電解液の気化によるスウェリング現象を抑制し、分離膜の収縮を抑制することによって電池の短絡、発熱および爆発を防止することができる安全性が改善されたリチウム二次電池を提供する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022740000001_ABST
    Figure 2025022740000001_ABST
Patent Text Reader

Abstract

To provide liquid electrolyte enabling materialization of excellent safety of a battery, and a lithium secondary battery including the liquid electrolyte.SOLUTION: A liquid electrolyte includes lithium salt, non-aqueous organic solvent, and an additive agent. The additive agent includes polymer expressed by the following chemical formula 1. [Chemical Formula 1] In the chemical formula 1, each of R1 to R3 is a dependent alkyl group of hydrogen, fluorine, or 1 to 10 of substituted or unsubstituted carbon, and each of n and m is a mole fraction, and satisfies inequality 50 mol%≤n≤90 mol%, and 10 mol%≤m≤50 mol%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a liquid electrolyte and a lithium secondary battery containing the same. [Background technology]

[0002] Lithium secondary batteries are rechargeable and have more than three times the energy density per unit weight compared to conventional lead-acid batteries, nickel-cadmium batteries, nickel-metal hydride batteries, and nickel-zinc batteries, allowing for fast charging. As a result, they have been commercialized for use in laptops, mobile phones, power tools, and electric bicycles, and research and development is being actively conducted to further improve their energy density.

[0003] Such a lithium secondary battery is used by injecting an electrolyte into a battery cell including a positive electrode including a positive electrode active material capable of intercalating and deintercalating lithium, and a negative electrode including a negative electrode active material capable of intercalating and deintercalating lithium.

[0004] The electrolytes of currently commercially available lithium secondary batteries use organic carbonate-based solvents in order to withstand high operating voltages.

[0005] However, organic carbonate-based solvents are highly volatile and flammable, and have a low flash point. When vaporized at high temperatures, they can cause the battery to swell and the polyethylene (PE) separator to melt down, posing a safety risk to the lithium secondary battery.

[0006] In order to solve the safety problems of lithium secondary batteries, extensive research is being conducted on separators, current collectors, active materials, and battery managing systems (BMS). However, as long as highly flammable organic solvents are used, it is not easy to solve the problems. In fact, the safety problems of lithium secondary batteries have been actively discussed recently due to the frequent occurrence of electric vehicle fires, and in particular, a solution from the perspective of electrolytes is needed to solve the fundamental problems. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Korean Patent Publication No. 10-2021-0018153 Summary of the Invention [Problem to be solved by the invention]

[0008] One embodiment provides a liquid electrolyte that can provide superior battery safety.

[0009] Another embodiment provides a lithium secondary battery including the liquid electrolyte. [Means for solving the problem]

[0010] According to an embodiment of the present invention, there is provided a liquid electrolyte comprising a lithium salt, a non-aqueous organic solvent, and an additive, the additive comprising a polymer represented by the following Chemical Formula 1: [Chemical formula 1] [ka] In chemical formula 1, R 1 ~R 3 each independently represents hydrogen, fluorine, or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, n and m are mole fractions, and 50 mol%≦n≦90 mol%, and 10 mol%≦m≦50 mol%, respectively.

[0011] A lithium secondary battery according to another embodiment of the present invention includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and the liquid electrolyte. Effect of the Invention

[0012] To provide a lithium secondary battery with improved safety, which can prevent short circuit, heat generation and explosion of the battery by blocking ion conduction of the battery when a problem occurs, suppressing swelling caused by evaporation of the electrolyte, and suppressing contraction of the separator. [Brief description of the drawings]

[0013] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment of the present invention; [Diagram 2] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment of the present invention; [Diagram 3] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment of the present invention; [Figure 4] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment of the present invention; [Diagram 5] 1 is a graph showing discharge capacity and coulombic efficiency according to the progress of high-temperature charge / discharge cycles for a lithium secondary battery. [Figure 6] 1 is a graph showing the results of a hot-box test of a pouch full cell. [Figure 7] 1 is a graph showing the results of TGA analysis of a liquid electrolyte according to an embodiment of the present invention. [Figure 8] The graph shows the results of measuring the DC resistance of a cell that was maintained for one hour at room temperature (25°C) and at a high temperature (120°C). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention is not limited to the embodiments described herein, but may be embodied in many different forms, and should not be construed as limited to the embodiments set forth herein.

[0015] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.

[0016] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.

[0017] It should be understood that, as used herein, the terms "comprise", "comprise", or "have" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.

[0018] Unless otherwise defined herein, the particle size may be the average particle size. In addition, the average particle size refers to the average particle size (D50) which means the diameter of particles with a cumulative volume of 50% by volume in the particle size distribution. The average particle size (D50) can be measured by a method widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by measuring with a transmission electron microscope or a scanning electron microscope. In another method, the average particle size (D50) value can be obtained by measuring with a measuring device using a dynamic light-scattering method, performing data analysis to count the number of particles for each particle size range, and then calculating from this. Alternatively, the average particle size (D50) can be measured using a laser diffraction method. When measuring by the laser diffraction method, more specifically, the particles to be measured are dispersed in a dispersion medium, then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT3000) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, after which the average particle size (D50) based on the 50% standard of the particle size distribution in the measuring device can be calculated.

[0019] In the drawings, the thickness of the various layers and regions is exaggerated for clarity, and similar parts are given the same reference numerals throughout the specification. When a part such as a layer, film, region, plate, etc. is said to be "on" or "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.

[0020] In addition, in this specification, the term "layer" includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.

[0021] As used herein, "or" is not to be construed in an exclusive sense, for example "A or B" is to be construed as including A, B, A+B, etc.

[0022] The term "metal" is interpreted as including general metals, transition metals and metalloids.

[0023] In this specification, unless otherwise defined, the term "substituted" means that at least one hydrogen atom in a substituent or a compound is replaced with deuterium, a halogen group, a hydroxyl group, an amino group, a substituted or unsubstituted amine group having 1 to 30 carbon atoms, a nitro group, a substituted or unsubstituted silyl group having 1 to 40 carbon atoms, an alkyl group having 1 to 30 carbon atoms, an alkylsilyl group having 1 to 10 carbon atoms, an arylsilyl group having 6 to 30 carbon atoms, a cycloalkyl group having 3 to 30 carbon atoms, a heterocycloalkyl group having 3 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, a heteroaryl group having 2 to 30 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a fluoroalkyl group having 1 to 10 carbon atoms, a cyano group, or a combination thereof.

[0024] In one embodiment of the present invention, "substitution" means that at least one hydrogen atom in a substituent or compound is substituted with deuterium, a halogen group, an alkyl group having 1 to 30 carbon atoms, an alkylsilyl group having 1 to 10 carbon atoms, an arylsilyl group having 6 to 30 carbon atoms, a cycloalkyl group having 3 to 30 carbon atoms, a heterocycloalkyl group having 3 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, a heteroaryl group having 2 to 30 carbon atoms, a fluoroalkyl group having 1 to 10 carbon atoms, or a cyano group. In one specific embodiment of the present invention, "substitution" means that at least one hydrogen atom in a substituent or compound is substituted with deuterium, a halogen group, an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, a fluoroalkyl group having 1 to 10 carbon atoms, or a cyano group. In one specific embodiment of the present invention, "substitution" means that at least one hydrogen atom in a substituent or compound is substituted with deuterium, a halogen group, an alkyl group having 1 to 5 carbon atoms, an aryl group having 6 to 18 carbon atoms, a fluoroalkyl group having 1 to 5 carbon atoms, or a cyano group. In addition, in a specific example of the present invention, "substituted" means that at least one hydrogen atom in a substituent or compound is replaced with deuterium, a cyano group, a halogen group, a methyl group, an ethyl group, a propyl group, a butyl group, a phenyl group, a biphenyl group, a terphenyl group, a trifluoromethyl group, or a naphthyl group.

[0025] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, and other types according to their shapes. FIGS. 1 to 4 are schematic diagrams showing a lithium secondary battery according to an embodiment, in which FIG. 1 shows a circular type, FIG. 2 shows a square type, and FIGS. 3 and 4 show a pouch type. Referring to FIGS. 1 to 4, the lithium secondary battery 100 may include an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown). The lithium secondary battery 100 may include a sealing member 60 that seals the case 50 as shown in FIG. 1. Also, the lithium secondary battery 100 in FIG. 2 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. As shown in FIGS. 3 and 4, the lithium secondary battery 100 may include electrode taps 70, i.e., a positive electrode tap 71 and a negative electrode tap 72, which serve as electrical paths for conducting the current generated in the electrode assembly 40 to the outside.

[0026] The electrolyte according to one embodiment will be described below.

[0027] The electrolyte according to an embodiment of the present invention is a liquid electrolyte and includes a lithium salt, a non-aqueous organic solvent, and an additive, and the additive may include a polymer represented by the following Chemical Formula 1. [Chemical formula 1] [ka] In chemical formula 1, R 1 ~R 3 each independently represents hydrogen, fluorine, or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, n and m are mole fractions, and 50 mol%≦n≦90 mol%, and 10 mol%≦m≦50 mol%, respectively.

[0028] The polymer represented by Chemical Formula 1 gels through crystallization in the liquid electrolyte when exposed to high temperatures of over 100℃, thereby preventing the evaporation of the electrolyte and the resulting expansion of the battery. It also blocks the ionic and electronic conduction of the battery, and through the mechanism of physically fixing the PE separator, which melts and shrinks at about 140℃, it prevents the sudden release of energy due to direct contact between the positive and negative electrodes, i.e., a short circuit, and thereby prevents fires and explosions, thereby improving the safety of the battery.

[0029] In particular, the polymer represented by Chemical Formula 1 is in a dispersed state in a liquid electrolyte before problems such as high temperature and impact occur, and since the electrolyte containing the polymer represented by Chemical Formula 1 is a liquid electrolyte, the electrolyte phase has a different structure from a solid electrolyte formed by polymerizing the polymer together with a polymerization initiator.

[0030] In the case of a solid electrolyte, since the electrolyte exists in a solid state within the battery, it has low ionic conductivity, low output, and short life, which is expected to be significantly different in terms of effectiveness from the battery using the liquid electrolyte according to the present invention.

[0031] As an example, n and m may be such that n:m is 80 mol %:20 mol % to 60 mol %:40 mol % or 80 mol %:20 mol % to 70 mol %:30 mol %.

[0032] The higher the content of vinylidene fluoride structural units in the polymer relative to the content of trifluoroethylene structural units, the more effectively the safety of the battery is improved.

[0033] The molecular weight of the polymer may be from 100,000 g / mol to 400,000 g / mol.

[0034] As an example, the molecular weight of the polymer may be from 200,000 g / mol to 400,000 g / mol.

[0035] The polymer may be in particulate form with an average particle size of 10 nm to 1 μm.

[0036] As an example, the average particle size of the polymer may be 10 nm to 900 nm, 10 nm to 800 nm, 10 nm to 700 nm, or 10 nm to 600 nm.

[0037] As an example, the average particle size of the polymer may be 30 nm to 1 μm, 50 nm to 1 μm, 100 nm to 1 μm, 100 nm to 900 nm, 100 nm to 800 nm, 100 nm to 700 nm, or 100 nm to 600 nm.

[0038] The polymer may be in a particulate phase, and when the average particle size is within the above range, precipitation of the polymer in the electrolyte can be alleviated, thereby reducing capacity loss due to repeated cycles.

[0039] As an example, R in Formula 1 1 ~R 3 may each independently be hydrogen or a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms.

[0040] As an example, the polymer may be poly(vinylidene fluoride-co-trifluoroethylene).

[0041] The polymer may be gelled at a temperature of 100°C to 120°C.

[0042] For example, the polymer may be included in an amount of 0.1 to 15 parts by weight based on 100 parts by weight of the total liquid electrolyte.

[0043] Specifically, the polymer may be included in an amount of 0.5 to 15 parts by weight, for example, 1 to 15 parts by weight, or 5 to 15 parts by weight, based on 100 parts by weight of the total liquid electrolyte.

[0044] When the content of the polymer is within the above range, a lithium secondary battery having improved safety can be realized by preventing an increase in resistance at high temperatures while ensuring life characteristics and output characteristics.

[0045] The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can migrate.

[0046] As the non-aqueous organic solvent, a carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvent can be used.

[0047] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, decanolide, mevalonolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc. In addition, cyclohexanone and the like can be used as the ketone solvent. In addition, ethyl alcohol, isopropyl alcohol and the like can be used as the alcohol solvent. R 1 -CN(R 1 (wherein R is a hydrocarbon group having 2 to 20 carbon atoms and having a linear, branched, or cyclic structure, and may contain a double bond, aromatic ring, or ether bond), nitriles such as dimethylformamide, amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes can be used.

[0048] The non-aqueous organic solvent may be used alone or in combination with one or more other solvents. When one or more other solvents are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which should be widely understood by those skilled in the art.

[0049] The non-aqueous organic solvent according to one embodiment of the present invention may contain a cyclic carbonate and a linear carbonate (cyclic carbonate:linear carbonate) in a volume ratio of 10:90 vol % to 50:50 vol %.

[0050] Specifically, the non-aqueous organic solvent may contain a cyclic carbonate and a linear carbonate in a volume ratio of 10:90 vol% to 40:60 vol%, for example, a volume ratio of 10:90 vol% to 30:70 vol%, or a volume ratio of 10:90 vol% to 25:75 vol%.

[0051] In the non-aqueous organic solvent having the above composition, the polymer in the liquid electrolyte gels at a certain temperature or higher, increasing the viscosity of the electrolyte and the resistance. As the gelled polymer increases, it acts as an insulator to block the ionic and electronic conduction of the battery, thereby ensuring the safety of the battery.

[0052] The liquid electrolyte may further include at least one other additive selected from the group consisting of vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, vinylethylene carbonate (VEC), adiponitrile (AN), succinonitrile (SN), 1,3,6-hexanetricyanide (HTCN), propene sultone (PST), propane sultone (PS), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), and 2-fluorobiphenyl (2-FBP).

[0053] By further including other additives, the life span can be further improved or gas generated from the positive and negative electrodes during high temperature storage can be effectively controlled.

[0054] The other additives may be included in an amount of 0.2 to 20 parts by weight, specifically 0.2 to 15 parts by weight, for example 0.2 to 10 parts by weight, based on 100 parts by weight of the total electrolyte for lithium secondary batteries.

[0055] When the content of other additives is within the above range, the increase in film resistance can be minimized, thereby contributing to improved battery performance.

[0056] Lithium salts are substances dissolved in organic solvents and act as a source of lithium ions in batteries to enable basic lithium secondary battery operation and to facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide (LiFSI)), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).

[0057] Another embodiment of the present invention provides a lithium secondary battery comprising a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and the liquid electrolyte described above.

[0058] The positive electrode includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, and may optionally further include a binder and / or a conductive material.

[0059] The positive electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium (lithiated intercalation compound). Specifically, one or more of composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof may be used.

[0060] The composite oxide may be a lithium transition metal composite oxide, and specific examples include lithium nickel-based oxides, lithium cobalt-based oxides, lithium manganese-based oxides, lithium iron phosphate-based compounds, cobalt-free nickel-manganese-based oxides, or combinations thereof.

[0061] As an example, a compound represented by any one of the following chemical formulas can be used: a A 1-b X b O 2-c D c (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05);Li a Mn 2-b X b O 4-c D c (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05);Li a Ni 1-b-c Co b X c O 2-α D α (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.5, 0<α<2);Li a Ni 1-b-c Mn b X c O 2-α D α (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.5, 0<α<2);Li a Ni b Co c L 1 d G eO2(0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, 0≦e≦0.1);Li a NiG b O2(0.90≦a≦1.8, 0.001≦b≦0.1);Li a CoG b O2(0.90≦a≦1.8, 0.001≦b≦0.1);Li a Mn 1-b G b O2(0.90≦a≦1.8, 0.001b≦0.1);Li a Mn2G b O4(0.90≦a≦1.8, 0.001≦b≦0.1);Li a Mn 1-g G g PO4(0.90≦a≦1.8, 0≦g≦0.5);Li (3-f) Fe2(PO4)3(0≦f≦2);Li a FePO4(0.90≦a≦1.8).

[0062] In the above chemical formula, A is Ni, Co, Mn, or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; L 1 is Mn, Al or a combination thereof.

[0063] For example, the positive electrode active material may be a high-nickel-based positive electrode active material in which the nickel content is 80 mol% or more, 85 mol% or more, 90 mol% or more, 91 mol% or more, or 94 mol% or more and 99 mol% or less relative to 100 mol% of metals excluding lithium in a lithium transition metal composite oxide. The high-nickel-based positive electrode active material can achieve high capacity and can be applied to high-capacity, high-density lithium secondary batteries.

[0064] The content of the positive electrode active material may be 90% by weight to 99.9% by weight, based on 100% by weight of the positive electrode active material layer, and the contents of the binder and conductive material may be 0.1% by weight to 5% by weight, based on 100% by weight of the positive electrode active material layer.

[0065] The binder serves to adhere the positive electrode active material particles to each other well and to adhere the positive electrode active material to the positive electrode current collector well. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.

[0066] The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not cause chemical changes in the battery that is constructed and is electronically conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes, metal-based materials in the form of metal powders or metal fibers including copper, nickel, aluminum, and silver, conductive polymers such as polyphenylene derivatives, and mixtures thereof.

[0067] The positive electrode current collector can be made of Al, but is not limited to this.

[0068] The negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, and may optionally further include a binder and / or a conductive material.

[0069] The negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material dopable and dedopable with lithium, or a transition metal oxide.

[0070] Examples of the material capable of reversibly intercalating / deintercalating lithium ions include carbon-based negative electrode active materials, which can include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of crystalline carbon include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, and the like.

[0071] As the alloy of lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.

[0072] As the material dopable and dedopable with lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. The Si-based negative electrode active material can be silicon, a silicon-carbon composite, SiO x (0 < x < 2), an Si-Q alloy (Q is selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO2, an Sn-based alloy, or a combination thereof.

[0073] The silicon-carbon composite may be a composite of silicon and amorphous carbon. According to an embodiment, the silicon-carbon composite may be in the form of silicon particles and the surfaces of the silicon particles coated with amorphous carbon. For example, it may include secondary particles (cores) formed by granulating primary silicon particles and an amorphous carbon coating layer (shell) located on the surfaces of the secondary particles. The amorphous carbon may also be located between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be dispersed in the amorphous carbon matrix.

[0074] The silicon-carbon composite may further comprise crystalline carbon. For example, the silicon-carbon composite may comprise a core comprising crystalline carbon and silicon particles and an amorphous carbon coating layer located on the core.

[0075] The Si-based negative electrode active material or the Sn-based negative electrode active material can be used in combination with a carbon-based negative electrode active material.

[0076] For example, the negative electrode active material layer can contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0% to 5% by weight of the conductive material.

[0077] The binder serves to adhere the negative electrode active material particles to each other and to the current collector well. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0078] Non-aqueous binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymers, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or combinations thereof.

[0079] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0080] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. The cellulose-based compound may be a mixture of one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof. The alkali metal may be Na, K, or Li.

[0081] The dry binder may be a fiberizable polymeric material such as polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0082] The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not cause chemical changes in the battery that is constructed and is electronically conductive can be used. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube, metal-based materials in the form of metal powder or metal fiber including copper, nickel, aluminum, and silver, conductive polymers such as polyphenylene derivatives, and mixtures thereof.

[0083] The negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0084] Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. Such separators can be polyethylene, polypropylene, polyvinylidene fluoride, or multi-layered films of two or more of these, and of course mixed multi-layered films such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator can also be used.

[0085] The separator can include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.

[0086] The porous substrate may be a polymer membrane formed from any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene, or a copolymer or mixture of two or more of these.

[0087] The organic material may include a polyvinylidene fluoride-based polymer or a (meth)acrylic-based polymer.

[0088] The inorganic materials may include, but are not limited to, inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof.

[0089] The organic material and the inorganic material may be mixed in one coating layer, or a coating layer containing an organic material and a coating layer containing an inorganic material may be laminated.

[0090] Examples and comparative examples of the present invention will be described below. However, the following examples are merely examples of the present invention, and the present invention is not limited to the following examples. EXAMPLES

[0091] (Example: Preparation of Lithium Secondary Battery) Example 1 LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2, polyvinylidene fluoride as a binder, and acetylene black as a conductive material were mixed in a weight ratio of 97.5:1:1.5, and dispersed in N-methylpyrrolidone to prepare a positive electrode active material slurry.

[0092] The positive electrode active material slurry was coated on an aluminum (Al) foil having a thickness of 15 μm, dried at 100° C., and then pressed to prepare a positive electrode.

[0093] Artificial graphite was used as the negative electrode active material, and the negative electrode active material was mixed with a styrene-butadiene rubber binder and carboxymethyl cellulose in a weight ratio of 98:1:1, respectively, and dispersed in distilled water to prepare a negative electrode active material slurry.

[0094] The negative electrode active material slurry was coated on a copper (Cu) foil having a thickness of 10 μm, dried at 100° C., and then pressed to prepare a negative electrode.

[0095] The prepared positive and negative electrodes were assembled with a 10 μm thick polyethylene separator to manufacture an electrode assembly, and a liquid electrolyte was injected to manufacture a lithium secondary battery.

[0096] The composition of the liquid electrolyte is as follows: (liquid electrolyte composition) Lithium salt: LiPF61.15M Non-aqueous organic solvent: ethylene carbonate: ethyl methyl carbonate: dimethyl carbonate (EC:EMC:DMC=20:40:40 volume ratio) Additives: (1) Polymer: Solvene(R)200 / P200 (Mw=200,000, n:m=80:20; Solvay) 15 parts by weight, (2) 1 part by weight of vinylene carbonate (VC) (However, in the electrolyte composition, "parts by weight" refers to the relative weight of the additive to the total weight of the electrolyte (lithium salt + non-aqueous organic solvent) excluding the additive.)

[0097] Example 2 A lithium secondary battery was produced in the same manner as in Example 1, except that Solvene(R) 200 / P400 (Mw=400,000, n:m=80:20; Solvay) was used instead of Solvene(R) 200 / P200.

[0098] Example 3 A lithium secondary battery was produced in the same manner as in Example 1, except that Solvene® 250 / P400 (Mw=400,000, n:m=75:25; Solvay) was used instead of Solvene® 200 / P200.

[0099] (Examples 4 and 5) Lithium secondary batteries were fabricated in the same manner as in Example 1, except that the liquid electrolytes were prepared by changing the content of the polymer to 5 parts by weight and 10 parts by weight, respectively.

[0100] Comparative Example 1 A lithium secondary battery was produced in the same manner as in Example 1, except that no polymer was used.

[0101] Comparative Example 2 A lithium secondary battery was produced in the same manner as in Example 1, except that a composition containing 1 g of a polymer (Solvene(R)200 / P200) and 0.5 g of a polymerization initiator (AIBN) was added to 95.5 g of a non-aqueous organic solvent (ethylene carbonate:ethyl methyl carbonate:dimethyl carbonate = 20:40:40 volume ratio) in which 1.15M LiPF6 and 1 part by weight of vinylene carbonate (VC) were dissolved, and heated at 60°C for 24 hours to form a gel polymer electrolyte.

[0102] (Evaluation 1: High temperature (45℃) life characteristics evaluation) The lithium secondary batteries produced in Examples 1, 4, and 5, and Comparative Example 1 were charged and discharged for 3 cycles at 1C, and then charged and discharged at 1C for 50 cycles to evaluate the discharge capacity and coulombic efficiency of the batteries. The evaluation results are shown in Figure 5. The voltage range used here was 3.0V to 4.2V (discharge to 3.0V, charge to 4.2V), and the evaluation temperature was 45°C.

[0103] FIG. 5 is a graph showing the discharge capacity and coulombic efficiency of a lithium secondary battery as a function of the progress of high-temperature charge / discharge cycles.

[0104] 5, it can be seen that the liquid electrolyte containing the polymer according to the present invention maintains the same or higher discharge capacity and coulombic efficiency compared to the liquid electrolyte not containing the polymer. From this evaluation result, it is predicted that the life characteristics of the battery will be maintained at an excellent level without deterioration.

[0105] (Rating 2: Hotbox rating) The pouch full cells of Examples 1 to 5 and Comparative Example 1 were subjected to a formation cycle, charged to SOC50 (3.94 V), and then exposed to silicone oil at 130° C. for 5 minutes, and the extent of volume expansion was compared. The evaluation results are shown in FIG.

[0106] FIG. 6 is a graph showing the results of a hot-box test of the pouch full cell.

[0107] 6, in the pouch cell not including a polymer (Comparative Example 1), the pouch cell was torn due to volume expansion caused by gasification of the electrolyte, but in the pouch cell including a polymer (Example), the degree of volume expansion was mitigated by suppressing gasification of the electrolyte. In other words, it can be seen that the thermal safety is improved even in a high-temperature storage environment in the case of a liquid electrolyte including a polymer.

[0108] (Evaluation 3: TGA (Thermo Gravimetric Analysis) Evaluation) In order to measure the weight change of the material due to the temperature change, TGA analysis was carried out on Example 1, Comparative Example 1, and Comparative Example 2. The evaluation results are shown in FIG.

[0109] FIG. 7 is a graph showing the results of TGA analysis of a liquid electrolyte according to an embodiment of the present invention.

[0110] 7, in the case of the liquid electrolyte according to Example 1, the TGA analysis result shows that the temperature at which the mass is halved at room temperature due to vaporization and thermal decomposition is 124°C, which is 42°C higher than the temperature (82°C) at which the mass of the liquid electrolyte (not including polymer) according to Comparative Example 1 is halved. This shows that when the liquid electrolyte in which the polymer is dissolved is introduced, the organic solvent participates in dissolving the polymer, causing an increase in the boiling point due to the van der Waals force between the polymer and the solvent, which delays the vaporization of the electrolyte at high temperatures and delays the expansion of the battery and the explosion due to the increase in internal pressure.

[0111] Meanwhile, when the polymer itself was evaluated, the mass did not decrease by half. Therefore, in the case of Comparative Example 2 in which a gel polymer electrolyte was used, it was confirmed that the effects of the present invention, such as delaying the evaporation of the electrolyte and delaying the explosion due to battery expansion and internal pressure increase, could not be expected.

[0112] (Evaluation 4: High temperature DC resistance (DC-IR) characteristic evaluation) For the lithium secondary batteries prepared in Example 1 and Comparative Example 1, the initial DC resistance (DCIR) was measured in terms of ΔV / ΔI (change in voltage / change in current) value, and then the maximum energy state inside the battery was set to a fully charged state (SOC 100%), and the DC resistance was measured at room temperature (25°C) in this state, and the DC resistance of the cell that was maintained for 1 hour after reaching a high temperature (120°C) was measured. The evaluation results are shown in Figure 8.

[0113] FIG. 8 shows the results of measuring the DC resistance of a cell that was maintained for one hour at room temperature (25° C.) and at a high temperature (120° C.).

[0114] Referring to FIG. 8, the battery using the liquid electrolyte according to Example 1 has a large increase in resistance due to gelation of the electrolyte when the temperature is increased to 120° C., and it is expected that the gelled electrolyte acts as an insulator between the positive and negative electrodes, thereby reducing the risk of sudden energy release, explosion, and fire due to a short circuit between the positive and negative electrodes.

[0115] (Evaluation 5: DC resistance (DC-IR) characteristic evaluation after exposure to high temperature) For the lithium secondary batteries prepared in Example 1 and Comparative Example 2, the initial DC internal resistance (DC-IR) was measured in terms of ΔV / ΔI (change in voltage / change in current) value, and then the maximum energy state inside the battery was set as a fully charged state (SOC 100%), and the DC internal resistance was measured at room temperature (25°C) in this state, and the DC internal resistance was measured after leaving it at a high temperature (60°C) for 5 days. The evaluation results are shown in Table 1.

[0116] [Table 1]

[0117] Referring to Table 1, when the gel polymer is formed (Comparative Example 2), an increase in resistance already occurs at 50°C to 60°C where the initiator is activated, and the resistance value of the cell when left at high temperature is higher than that of the Examples. In addition, an additional increase in resistance occurs due to the increase in resistance caused by the continuous crosslinking reaction, and as a result, the resistance increase rate is much higher than that of the Examples.

[0118] On the other hand, since the polymer in the liquid electrolyte according to the embodiment is gelled at temperatures of 100° C. to 120° C., the increase in resistance due to gelling hardly occurs at 60° C., and the resistance when left at 60° C. is relatively low.

[0119] Thus, in the liquid electrolyte containing the polymer additive according to the present invention, the polymer is crystallized at high temperatures, causing the liquid electrolyte to gel. The gelled liquid electrolyte forms a solid film and acts as an insulator, blocking ionic and electrical conduction between the positive and negative electrodes, thereby preventing fires and explosions in the battery.

[0120] In addition, the gelled liquid electrolyte physically bonds the positive electrode, separator, and negative electrode together, thereby suppressing the separator's high-temperature shrinkage, and thereby preventing short circuits between the positive and negative electrodes.

[0121] Although a preferred embodiment of the present invention has been described above, the present invention is not limited thereto, and can be embodied in various modified forms within the scope of the claims, the detailed description of the invention, and the attached drawings, which of course also fall within the scope of the present invention. [Explanation of symbols]

[0122] 100: Lithium secondary battery 10: Positive electrode 11: Positive lead tap 12: Positive terminal 20: Negative electrode 21: Negative lead tap 22: Negative terminal 30: Separator 40: Electrode assembly 50: Case 60: Sealing material 70: Electrode tap 71: Positive tap 72: Negative tap

Claims

1. A lithium salt, a non-aqueous organic solvent, and an additive, The additive comprises a liquid electrolyte comprising a polymer represented by the following formula 1: [Chemical formula 1] 【Chemistry 1】 In the above Chemical Formula 1, R 1 ~R 3 each independently represents hydrogen, fluorine, or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, n and m are mole fractions, and 50 mol%≦n≦90 mol%, and 10 mol%≦m≦50 mol%, respectively.

2. 2. The liquid electrolyte according to claim 1, wherein n and m are in the range of 80 mol%:20 mol% to 60 mol%:40 mol%.

3. The liquid electrolyte according to claim 1, wherein the molecular weight of the polymer is from 100,000 g / mol to 400,000 g / mol.

4. The liquid electrolyte of claim 1 , wherein the polymer is in a particulate phase having an average particle size of 10 nm to 1 μm.

5. R of Formula 1 1 ~R 3 The liquid electrolyte according to claim 1, wherein each independently represents hydrogen or a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms.

6. The liquid electrolyte of claim 1 , wherein the polymer is poly(vinylidene fluoride-co-trifluoroethylene).

7. The liquid electrolyte of claim 1 , wherein the polymer is gelled at a temperature of 100° C. to 120° C.

8. The liquid electrolyte of claim 1, wherein the polymer is contained in an amount of 0.1 to 15 parts by weight based on 100 parts by weight of the total liquid electrolyte.

9. 2. The liquid electrolyte of claim 1, wherein the non-aqueous organic solvent comprises a cyclic carbonate and a linear carbonate in a volume ratio of 10:90 vol% to 50:50 vol%.

10. The liquid electrolyte may be any of vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, vinylethylene carbonate (VEC), adiponitrile (AN), succinonitrile (SN), 1,3,6-hexanetricyanide (HTCN), propene sultone (PST), propane sultone (PS), lithium tetrafluoroborate (LiBF 4 ), lithium difluorophosphate (LiPO 2 F 2 2. The liquid electrolyte of claim 1, further comprising at least one other additive selected from the group consisting of 2-fluorobiphenyl (2-FBP), ... and 2-fluorobiphenyl (2-FBP).

11. a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; and A lithium secondary battery comprising the liquid electrolyte according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Solid polymer electrolyte and preparation method and application thereof

    CN114678589A

  • Secondary battery with organic electrolyte

    JP1994119939A

  • Nonaqueous electrolytic lithium secondary cell

    JP1996050923A

  • Secondary battery

    JP2000182668A

  • Method of producing elastomer particle

    JP2001253948A